2017
DOI: 10.1186/s12862-017-0976-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body size evolution and ecology on encephalization in cave bears and extant relatives

Abstract: BackgroundThe evolution of larger brain volumes relative to body size in Mammalia is the subject of an extensive amount of research. Early on palaeontologists were interested in the brain of cave bears, Ursus spelaeus, and described its morphology and size. However, until now, it was not possible to compare the absolute or relative brain size in a phylogenetic context due to the lack of an established phylogeny, comparative material, and phylogenetic comparative methods. In recent years, many tools for compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 98 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…In sum, using one of the largest mammalian brain size data set to date, we found that hibernators have significantly smaller brain sizes relative to body mass than nonhibernating species overall (species‐level), and within five of seven orders. This result adds to numerous previous studies supporting the idea that experienced seasonality ( in extremis where hibernation is necessary for survival) imposes an energetic challenge and thus acts as an evolutionary constraint on brain size (van Woerden et al ., ; Jiang et al ., ; Weisbecker et al ., ; Luo et al ., ; Veitschegger, ). This energetic challenge imposed by the environment also provides one explanation why ectothermic species such as reptiles, amphibians, fishes and insects do have smaller brain size relative to body mass compared to endothermic species such as mammals and birds, as previously pointed out by Gillooly & McCoy ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, using one of the largest mammalian brain size data set to date, we found that hibernators have significantly smaller brain sizes relative to body mass than nonhibernating species overall (species‐level), and within five of seven orders. This result adds to numerous previous studies supporting the idea that experienced seasonality ( in extremis where hibernation is necessary for survival) imposes an energetic challenge and thus acts as an evolutionary constraint on brain size (van Woerden et al ., ; Jiang et al ., ; Weisbecker et al ., ; Luo et al ., ; Veitschegger, ). This energetic challenge imposed by the environment also provides one explanation why ectothermic species such as reptiles, amphibians, fishes and insects do have smaller brain size relative to body mass compared to endothermic species such as mammals and birds, as previously pointed out by Gillooly & McCoy ().…”
Section: Discussionmentioning
confidence: 99%
“…Support for this hypothesis derives not only from the present study but also from an intraspecific study in Andrew's toads ( Bufo andrewsi ), which found that populations with longer periods of hibernation had smaller brains (Jiang et al ., ). Furthermore, a study in extant and extinct bear species reveals that brain size is smaller in species that exhibit dormancy and have a low calorie diet (Veitschegger, ).…”
Section: Discussionmentioning
confidence: 99%
“…The unusually small size of bear cubs relative to the mother may be a result between natural selection’s strong emphasis on large adult body mass and the legacy effect of the small body size in bear ancestors. Interestingly, in the other obligate herbivorous member of Ursidae, the cave bear ( Ursus spelaeus ; Veitschegger, ), body size seems to be evolving at a faster rate than brain size, the latter of which also directly correlates with gestation time, neonatal mass and litter size (Finarelli, ).…”
Section: Discussionmentioning
confidence: 99%
“…The investigated haplotypes of cave bears exhibit different growth patterns indicating variation in life history strategy during early phases of speciation. There is evidence that cave bears had a faster life history compared to close relatives because of their smaller relative brain size [ 71 ]. However, the overall pace of growth reconstructed for cave bears in this study is similar to those of their close relatives.…”
Section: Discussionmentioning
confidence: 99%